PENGARUH EKSTENSIFIKASI DAN INTENSIFIKASI PAJAK TERHADAP PENERIMAAN PAJAK PENGHASILAN ORANG PRIBADI (Studi Pada Kantor Pelayanan Pajak Pratama Luwuk) - Delviana, Delviana; Tampang, Tampang; Mustamin, Mustamin; Halwi, Muhammad Darma; Masruddin, Masruddin; Din, Muhammad; Parwati, Ni Made Suwitri (Department of Accounting, Faculty of Economics and Business, Universitas Tadulako, 2021)
This study aims to examine and analyze the effect of tax extensification and intensification on personal income tax. The sample in this study is 36 tax authorities who work at Primary Tax Office of Luwuk. The method used to determine the number of samples is the purposive sampling. The research method is survey research. Data analysis technique uses descriptive analysis and multiple linear regression. The results of the study show that extensification has no positive effect on personal income tax, while tax intensification has positive effect on personal income tax.